1959
DOI: 10.1055/s-0038-1654383
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Formation in Purified Systems

Abstract: SummaryStudy of the kinetic behavior of purified human clotting factors suggests that formation of prothrombin activator from platelets, plasma thromboplastin component (PTC), antihemophilic factor (AHF), Factor V and calcium proceeds by a sequence of reactions. The earliest detectable reaction is slow and involves platelets, PTC and calcium; an intermediate activated PTC is obtained which is free of platelet contamination and is characterized by its kinetic behavior. Platelets are also requisite at a later st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1962
1962
1969
1969

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Fisch & Duckert (50), in 1959, concluded from the formation rate and yield of Product I in various mixtures, that Factors VIII and IX behave as substrates, and Factor X as an enzyme. The report of Surgenor et al (41) in the same year did not deal with Factor X, a new entity at that time, but it concluded that analy sis of the reactions leading to thrombin formation identified AHG as a sub strate, but Factor IX as behaving "in a distinctly different way." Biggs & Macfarlane [(2) p. 82] had doubts about Fisch & Duckert's selection of a substrate role for Factor IX; they pointed out that this factor is not con sumed during the coagulation process and so it is hard to view it as a sub strate.…”
Section: Reactions In the Formation Of The Intrinsic Prothrombin Actimentioning
confidence: 99%
“…Fisch & Duckert (50), in 1959, concluded from the formation rate and yield of Product I in various mixtures, that Factors VIII and IX behave as substrates, and Factor X as an enzyme. The report of Surgenor et al (41) in the same year did not deal with Factor X, a new entity at that time, but it concluded that analy sis of the reactions leading to thrombin formation identified AHG as a sub strate, but Factor IX as behaving "in a distinctly different way." Biggs & Macfarlane [(2) p. 82] had doubts about Fisch & Duckert's selection of a substrate role for Factor IX; they pointed out that this factor is not con sumed during the coagulation process and so it is hard to view it as a sub strate.…”
Section: Reactions In the Formation Of The Intrinsic Prothrombin Actimentioning
confidence: 99%